The search for Columbus' egg - finding a new formula to determine quotas at the IMF - Martin Skala; Christian Thimann; Regine Wölfinger (European Central Bank (ECB), 2007)
The International Monetary Fund (IMF) is undergoing profound changes, not only in its policies, but also in its internal governance. These changes reflect the structural developments in the global economy, and in particular the growing role of emerging economies that demand a greater say at the Fund. In addition, the Fund has recognised that it needs to strengthen the voice of developing economies in order to increase ownership of IMF programmes and policy recommendations from this very large country group. At the heart of IMF governance lies the distribution of its quota: quotas are the percent share at the IMF that are attributed to the various members. Quotas play a central role in the Fund, because they determine not only member countries' financial contributions, but also their rights to draw on IMF financial support and their voting rights within the institution. Therefore, quotas are essentially a matter of representation, visibility, and influence of countries at the IMF. Quotas are being calculated as a function of various economic variables and also include a certain degree of judgement. This paper provides a systematic analysis of the way IMF quota have been calculated in the past and of the current challenges of reform. It shows the importance for individual variables for specific country groups and the sensitivity of changes in the formula of overall distribution. The paper provides an extensive and comprehensive overview of various technical issues involved in choosing an appropriate quota formula. It analyses the current quota system and its functioning, and shows which countries and groups are most under and over-represented. It also puts forward an analysis of the various avenues of quota-reform that are currently under discussion.
Keywords: 330; Internationaler Kredit; Quotenregulierung; Welt